Irradiation effects of hydrogen and helium plasma on different grade tungsten materials. (August 2017) - Liu, X.; Lian, Y.Y.; Greuner, H.; Boeswirth, B.; Jin, Y.Z.; Feng, F.; Wang, J.B.; Chen, L.; Song, J.P.; Yu, Y.; Zhang, T.; Liu, C.S.; et al.
Highlights: The observed surface modifications don't closely correlate with the investigated W materials. Nano-structure seems not to be formed on the surface of the aggregated oxides and carbides phases. Sample temperature dominates the evolution of surface morphologies and 850 °C could be the critical temperature of pin-hole structure formation. H/He mixture pre-exposed will induce a significant decrease of the critical energy density for crack initiation under ELM-like repetitive loads, while no remarkable influence for only hydrogen pre-exposure. Abstract: Fine-grain tungsten alloys could be one of the solutions for the plasma facing materials of future DEMO reactors. In order to evaluate the service performances of the newly developed W alloys under edge plasma irradiation and the synergetic effect of fusion plasma together with high heat flux, both low energy He ions and high energy H, H/He mixed neutral beam irradiation on W-ZrC, W-K, W-Y2 O3, W-La2 O3 and CVD-W coating were performed respectively at a liner plasma facility (Dalian Nationality University, China) and the neutral beam facility GLADIS (IPP, Germany). Surface damages were characterized, and the crack formation and extension behaviors under ELM-like transient loading after H and H/He mixed beam irradiation were also investigated in the 60 kW EMS-60 facility (Electron beam Materials testing Scenario) at SWIP (Southwestern Institute of Physics, China). The experimental results indicated that surface damages induced by low or high energy H/He ion/neutral beam didn't closely correlate with the type of tungsten materials. However, H/He (6at% He concentration) neutral beam induced more significant surface damages of the tested W materials than only H neutral beam irradiation under the similar irradiation conditions. Similarly, the mixed H/He pre-exposure remarkably reduced the critical power of crack initiation compared with the un-irradiated samples under 100 repetitive loads of 1 ms pulse, while no significant degeneration for the case of only H beam irradiation was observed.